Vitamin D receptor gene polymorphisms in a group of postmenopausal Turkish women: association with bone mineral density - YOLDEMİR, AHMET TEVFİK; YAVUZ, DİLEK; ANIK İLHAN, GÖKÇE (INFORMA HEALTHCARE, 2011)
Objective To determine the frequency of the vitamin D receptor (VDR) gene polymorphisms BsmI, ApaI, TaqI and FokI and their associations with bone mineral density (BMD) in postmenopausal Turkish women. Design One hundred and thirty healthy postmenopausal women and 130 premenopausal healthy women acting as controls were included in the study. The BsmI, FokI, ApaI and TaqI polymorphisms in the VDR gene were studied by polymerase chain reaction-restriction fragment length polymorphism method. The BMD of the lumbar vertebrae and femur neck were measured by dual-energy X-ray absorptiometry. Comparisons between the groups were performed using the paired t-test and ANOVA. chi(2) or contingency tables were used to analyze qualitative results. Results Genotypes BB, Bb and bb occurred in premenopausal women with frequencies of 16.92%, 50% and 33.08% and in postmenopausal women with frequencies of 16.92%, 56.15% and 26.92%, respectively. Genotypes FF, Ff, ff occurred in premenopausal women with frequencies of 47.69%, 42.31% and 10% and in postmenopausal women with frequencies of 50.77%, 42.31% and 6.92%, respectively. Genotypes AA, Aa, aa occurred in premenopausal women with frequencies of 23.85%, 56.15% and 20% and in postmenopausal women with frequencies of 26.15%, 46.15% and 27.70%, respectively. Genotypes TT, Tt and tt occurred in premenopausal women with frequencies of 37.69%, 45.38% and 16.92% and in postmenopausal women with frequencies of 39.23%, 45% and 15.38%, respectively. There was no difference in the frequencies of VDR gene polymorphisms between premenopausal and postmenopausal women. BMD measurements were not different between genotypes in premenopausal and postmenopausal women. Conclusions The VDR gene BsmI, FokI, ApaI and TaqI polymorphisms have no major influence on bone mineral density in our group of postmenopausal women.
Keywords: POSTMENOPAUSE; BONE MINERAL DENSITY; VITAMIN D RECEPTOR GENE POLYMORPHISM; VDR GENE; TRANSLATION INITIATION SITE; START CODON POLYMORPHISM; JAPANESE WOMEN; PREMENOPAUSAL WOMEN; CALCIUM-ABSORPTION; AMERICAN WOMEN; CHINESE WOMEN; OSTEOPOROSIS; MASS; ESTROGEN